Spatial mobility on the border and the formation of spaces of life in Amazon: the case of cities twins of Guajará-Mirim (Brazil) and Guayaramerín (Bolivia) - Lira, Jonatha Rodrigo de Oliveira (Geografares, 2017)
This article has as main objective to analyze the space mobility in the frontier from the social dynamics of the twin cities of Guajará-Mirim (Brazil) and Guayaramerín (Bolivia). The Brazilian Demographic Census of 2010 demonstrates how international migration is configured in the Brazilian Amazon and from this information we identify the importance of the twin cities of this study. Thus, in terms of accumulated migration, Bolivia stands out with the largest volumes of foreigners in the Brazilian Amazon, concentrated mainly in municipalities along the border. The spatial configuration highlights the importance of twin cities such as Guajará-Mirim (Brazil) and Guayaramerín (Bolivia) in this dynamic. However, the porosity of the border is shaped by the mobility of people and not necessarily by migration. Due to mobility, Courgeau's concept of "living space" (1988) was used as a theoretical methodological proposal to integrate macro (regional scale) and micro (local scale) approaches as well as quantitative and qualitative approaches to rethinking the role of the frontier in Demographic dynamics. It is concluded that international migration and mobility at the border are complementary processes that help to understand the social dynamics of twin cities. In the sense that they articulate different scales of phenomena related to the spatial distribution of the population in the Brazilian Amazon, constituting spaces of life with specific characteristics configured by. the practice of transnational activities of those who reside there and use the frontier.Keywords: International  Mobility, Border, Life Spaces.